Friend or Foe: Prognostic and Immunotherapy Roles of BTLA in Colorectal Cancer - Song, Jingjing; Wu, Lihui (Frontiers in Molecular Biosciences, 2020)
Background: B and T lymphocyte attenuator (BTLA) is a co-signaling protein belonging to the CD28 immunoglobulin superfamily. However, the role of BTLA in prognosis and immunotherapy of colorectal cancer (CRC) remains unclear. Methods: We evaluated the expression of BTLA via the Oncomine and the cancer genome atlas (TCGA) database. We research the outcome among different BTLA expression patients by Kaplan-Meier curve. We used the Chi-Squared test and Cox regression analysis to identify potential risk factors. Besides, the correlations between BTLA and cancer immune infiltration were investigated via CIBERSORT. Results: Various cohorts showed that BTLA expression was lower in CRC compared to corresponding normal tissue. Moreover, low BTLA expression was correlated with poor overall survival (OS) in TCGA cohorts and GEO cohorts (GSE29623 and GSE17536). Low BTLA expression was associated with less lymph node metastasis (p = 0.0123). In the Cox proportional hazards model, BTLA was identified as a favorable prognostic factor. Naive B cells, memory B cells, CD8 T cells, CD4 memory resting T cells, follicular helper T (Tfh) cells, monocytes, resting natural killing (NK) cells, M0 macrophages, M1 macrophages, resting mast cells and activated mast cells were affected by BTLA expression (all p < 0.01). Correlated immune markers and functional enrichment analysis revealed BTLA functioned in the T cell receptor signaling pathway, B cell receptor signaling pathway, and NK cell-mediated cytotoxicity pathway. Conclusions: These analyses suggest BTLA is a potential factor for extended survival and closely related to CD8 T cells, Tfh cells, B cells, and NK cells in CRC. We summarize these results that BTLA can be used as a prognostic biomarker and might contribute to developing novel CRC immunological treatment strategies.